Efeitos do atipamezol e da ioimbina isolados ou em associação com a naloxona nda reversão anestésica de macacos bugios (Aloautta guariba clamitans) (CABRERA, 1940) anestesiados com metadona, dexmedetomidina e cetaminha S(+) - Monteiro, Sharlenne Leite da Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The present study addressed the effects caused by chemical restraint with methadone (0.1mg/kg), dexmedetomidine (5µg/kg) and ketamine S(+) (8 mg/kg) in Howley monkeys (Alouatta guariba clamitans) as well as the comparison of the quality and the time of the anesthetic reversal with isolated or associated narcotic α2-adrenergic antagonists in New world monkeys. Five adult and healthy Howley monkeys were used. The anesthetic protocol was administered via intramuscular. Five minutes after sedation, the animal was put on a table with thermal mattress where the following parameters were measured: cardiac and respiratory frequencies, rectal temperature, systolic arterial pressure and palpebral reflexes. These parameters were measured every 10 minutes. After 45 minutes of anesthesia a solution of NaCl 0.9% was administered to the control treatment, 25µg/kg of atipamezole for the ATI treatment, 0.5 mg/kg of yohimbine to the IOI treatment, atipamezole (25µg/kg) associated with naloxone (0.2 mg/kg) to the ATINALOX treatment and the IOINALOX treatment was composed of yohimbine (0.5 mg/kg) associated with naloxone (0.2 mg/kg), administered via intravenous in the primates' ulnar vein. After the reverser administration the animal was placed on a cage and the period of full recovery was evaluated by three researchers. The period of full recovery was determined from the antagonist administration until the patient's full recovery. The recovery was evaluated using scores that varied from zero (0) to three (3), accordingly to Galante, 2013. Some animals showed drooling after the intravenous administration of atipamezole and yohimbine. The association of methadone, dexmedetomidine and ketamine was effective to the chemical restraint of these animals allowing the performance of clinical procedures by up to 45 minutes. The IOINALOX treatment was the most effective regarding to time but the ATINALOX treatment gained the best recorvery

O presente estudo aborda os efeitos causados pela contenção química com metadona (0,1mg/kg), dexmedetomidina (5µg/kg) e cetamina S(+) (8mg/kg) em macacos bugios (Alouatta guariba clamitans), bem como compara a qualidade e o tempo na reversão anestésica com antagonistas α2-adrenérgicos isolados ou associados a antagonistas narcóticos em macacos do novo mundo. Foram utilizados cinco macacos bugios, adultos e hígidos. O protocolo anestésico foi aplicado, por via intramuscular. Cinco minutos após a sedação do animal, o mesmo foi colocado em mesa com colchão térmico, onde foram aferidos os seguintes parâmetros: frequência cardíaca, respiratória, temperatura retal, pressão arterial sistólica e reflexos palpebrais. Estes parâmetros foram aferidos em intervalos de 10 minutos. Após 45 minutos da anestesia, foi aplicado a solução NaCl 0,9% para o tratamento controle, 25µg/kg de atipamezol para o tratamento ATI, 0,5 mg/kg de ioimbina para o tratamento IOI, atipamezol (25µg/kg) com naloxona (0,2 mg/kg) para o tratamento ATINALOX e o tratamento IOINALOX composto de ioimbina (0,5 mg/kg) associado à naloxona (0,2 mg/kg), administrados, por via IV, na veia ulnar dos primatas. Após a aplicação do reversor, o animal foi colocado em uma gaiola para avaliação da recuperação feita por 3 pesquisadores. O período de recuperação total foi compreendido desde a aplicação do antagonista até a total recuperação do paciente. A recuperação foi avaliada utilizando-se escores variavam de zero (0) a três (3), de acordo com Galante (2013). Alguns animais apresentaram sialorréia após a aplicação IV de atipamezol e ioimbina. Concluiu-se que a associação de metadona, dexmedetomidina e cetamina foi eficaz para contenção química desses animais, permitindo a realização de procedimentos clínicos com duração de até 45 minutos. O tratamento IOINALOX foi mais eficaz no quesito tempo, porém o tratamento ATINALOX obteve a melhor
Effects of atipamezole and yohimbina isolated or in association with naloxine on the anesthetic reversal in Howley monkeys (Alaoutta guariba clamitans) (CABRERA, 1940) anesthetized with methadone, dexmedetomidine and ketamine S(+)
Keywords: Primatas não humanos; Inibidores quimicos; Opióides; Anestesicos - Efeito fisiologico; Anestesia veterinaria; Macaco; Anesthesia; Opioids